A Phenomenological Exploration of the Loss of a Parent in Childhood - Westwood, Rita; Harris, Juliet; West, Paul; Walker, Lynne (European Journal for Qualitative Research in Psychotherapy, 2007)
We investigated how the death of a parent, in childhood, represents a profound psychological insult. Although a number of studies have examined rates of depression and anxiety in bereaved children, less attention has been given to understanding predictors of children’s adjustment to the loss. Data collection involved a one-time semi-structured interview. Data are presented from 4 participants in which a parent had died. The participants were split into two groups those whose parent had died when they were under 7 and those over 7, the interviews being conducted by one of the researchers. Using multiple regression questions, potential predictors of children’s psychosocial adjustment to parental death are examined and their relative importance is discussed. Among the predictors considered were child’s age, child’s gender, deceased parent’s gender, time since death, length of illness, presence of siblings, sense of responsibility and parental communication patterns. The child’s perception of the surviving parent’s level of openness in parental communication was found to be significantly correlated with lower levels of depressive symptoms and state anxiety in bereaved children. The single man reported lower levels of depressive symptoms than did the women, and the participants reported lower levels of state anxiety as the years had passed.